PATTERN OF FRESH FRUIT BUNCH (FFB) PRODUCTION AND YIELD DISTRIBUTION OF OIL PALM IN ANDHRA PRADESH - P. MADHAVI LATHA *, M. TIRUPATI REDDY, B. PRATAP; H.P. MAHESWARAPPA (The Journal of Research ANGRAU, 2021)
The field study was conducted to evaluate new tenera hybrids at Horticultural Research Station, Vijayarai. As oil palm is a continuous fruit yielding crop in a harvest year, variations in month wise FFB production was studied in tenera hybrid crosses. The performance of hybrids under irrigated conditions planted during 2007 was studied for four years (9 to 12 years after planting) for bunch number, bunch weight and FFB production per ha at monthly intervals. During the four years of study, palms showed significant differences in bunch number, average bunch weight and FFB production in different months of a harvest year. Average bunch weight increased with increase in age of the palms during the study period from 6th to 9th harvest years (11.54 to 14.98 kg) with inverse relation between number of bunches produced per palm and average bunch weight. May, August and September were the months which recorded 40-45 % of total yield of a harvest year while November, December, January and February were the lean production months which recorded lower number of bunches palm-1 month-1(0.5) and lower bunch weights month-1 (4 to 5 kg) contributing to 10 % annual yield. Cumulative yield of 4 years data shows that there was 18 % and 15% FFB production recorded in May and August months, respectively. Four years mean FFB production was 3.5 t ha-1 in August followed by 3 t ha-1 in May month. In lean production months (November, December, January and February) per month FFB production was only 0.5 t ha-1. In Andhra Pradesh, peak oil palm FFB production season is 6 months (April to September) and the remaining 6 months (October to March) is lean period.